Women in the International Film Industry Policy, Practice and Power - Liddy, Susan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
The chapter Experiencing Male Dominance in Swedish Film Production is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Introduction -- The Gendered Landscape in International Film Production: Continuity and Change. Susan Liddy -- Europe -- The Austrian Film Gender Report 2012-2016. Eva Flicker and Lena Lisa Vogelmann -- Where are the Female Creatives? The Status Quo of the German Film Industry. Elizabeth Prommer and Skadi Loist -- With Eyes Wide Open: Gender Equality in the Polish Film Industry. Greta Gober -- The Road to 5050: Gender Equality and the Irish Film Industry. Susan Liddy -- Gender Equality in British Filmmaking: Research, Targets, Change. Shelley Cobb and Linda Ruth William -- Gendered Representation in Danish Film. Tess Sophie Skadegård Thorsen -- To Change or not to Change: Women and Gender Equality in the Finnish Film Industry. Tarja Savolainen -- From Edith to Carlmar to Iram Haq: Women in the Norwegian film industry. Anette Svane -- Experiencing Male Dominance in Swedish Film Production. Maria Jansson and Louise Wallenberg -- Out in the Cold? Women Filmmaker in Iceland. Gudrun Elsa Bragadottir -- Women in the Italian Film Industry: Against All Odds. Bernadette Luciano and Susanna Scarparo -- Gender Struggles in the Portuguese Film Industry (2008-2018). Carla Baptista and Ana Prata -- North America -- Hollywood and Gender Equity Debates in the #metoo Times Up Era. Courtney Brannon Donoghue -- Australia and New Zealand -- Gender Still Matters: Towards Sustainable Progress for Women in Australian Film and Television Industries. Lisa French -- Marian Evans Aotearoa New Zealand: A Tale of Two Nations -- Nigeria -- Women and Representation in Nollywood: Questions of Production and Direction. Agatha Ada Ukata.
Keywords: Motion pictures; Culture; Gender; Cultural policy; Film/TV Industry; Culture and Gender; Cultural Policy and Politics